Model Pembelajaran Sejarah Berpusat pada Siswa di MA dan SMA Kota Madiun - Dimas Aji Baramtara; Miftahuddin Miftahuddin (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
History learning at the MA and SMA levels is still dominated by conventional methods that are centered on teachers, making students less active, uninterested, and tend to just memorize the material. In fact, history learning should encourage students to think critically, understand the historical context, and reflect on past values ​​in today's life. Based on this, this study aims to determine the reasons for the need for a student-centered history learning model to be implemented in MA and SMA in Madiun City, how it is implemented, and what its influence and impact are on students. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The subjects of the study included history teachers, students, and principals at several MA and SMA in Madiun City. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that a student-centered history learning model needs to be implemented because the conventional approach is no longer relevant to the demands of the Merdeka Curriculum and the needs of 21st century learning. The implementation of this model is carried out through various active strategies such as group discussions, projects, and problem-based learning, with teachers as facilitators. The impact is that students become more motivated, active, and able to think critically and reflectively. This approach also improves cooperation, communication, and deeper understanding of historical materials. However, its implementation still faces obstacles in the form of limited time, teacher readiness, and supporting facilities.